Effects of Particulate Matter Exhaust on Functional Parameters of Organ Systems and Reactive Oxygen Species: A Cross-Sectional Study - Manjula Shivanagappa; SS Malini; Thanmayi Mahadeshwara Prasad; D. R. Mahadeshwara Prasad (Asia Pacific Journal of Medical Toxicology)
Background: From the day of industrial revolution and urbanization, exposure to diesel exhaust particles has become an environmental and occupational health concern as they contain a variety of nanoparticles which interfere with cellular function. Every organism on Earth has been exposed to minute foreign particles which enter the organ system and disrupt the cellular processes, interact with membranes, cell organelles, DNA, and other proteins to establish a series of dynamic bio-physico-chemical interactions. We aimed to study the variation in inflammatory cellular components and oxidative stress markers among exposures along with the variation in functional parameters of the organs involved in detoxifying these nanoparticles, the renal and hepatic system.Methods: After the ethical clearance from Institutional Ethical Committee, IHEC-UOM No. 123PhD/2016-17, a cross-sectional study was undertaken in Molecular Reproductive and Human Genetics Lab, Manasa Gangothri, University of Mysore, Mysore, Karnataka, India during 2015-2019, among 500 male garage workers of age group 18-60years with history of exposure for 6-8 hours a day without using any protective aids during work, for past 6-12 years and 300 controls, who live in areas where they were sparsely exposed. Serum oxidative stress markers, hemogram, renal and liver functional parameters were analysed.Results: A significant variation was observed among the oxidative stress markers among the exposures with surge in malondialdehyde and reduction in superoxide dismutase and catalase with variation in cell count, renal and liver functional parameters (p ≤ 0.05).Conclusion: Diesel combustion nanoparticles induces oxidative stress which reflects hepato-renal aberration.